Post-Traumatic Victimhood and Group Analytic Therapy: Intersubjectivity, Empathic Witnessing and Otherness. (September 2014) - Berman, Avi
Victimhood is part of the field of treatment of patients with post-traumatic disorder. Recovery processes may occur only within environments that recognize the suffering the person has endured. I refer to 'post-traumatic victimhood' as a self-state in the sense of the concept of multiple selves. I suggest that during the post-traumatic recovery process, the victimhood self-state may be fixated as a sub-character of a person or sometimes of an entire society. From within a post-traumatic victimhood self-state a certain pattern of interpersonal behaviour emerges: claiming recognition as a victim, displacement of victimhood aggression, transforming personal suffering into domination control and suspension of concern. The group may become a healing environment for a post-traumatic patient in which he/she may feel belonging, empathic witnessing and compassion from the other participants, as well as the group conductor. Victimhood aggression in the group may be expressed as complaints and accusations against another participant, or in the form of accusing others, or a sub-group, the whole group or the conductor. Group analytic therapy may become, therefore, highly intersubjective. The emotional involvement of the conductor and the participants alike pose a therapeutic challenge. 'Neutrality' and 'objectivity' seem beyond reach. Relevant relational concepts like 'empathic witnessing', 'otherness and sameness' and their therapeutic consequences are further discussed in the article.